2016
DOI: 10.1002/num.22057
|View full text |Cite
|
Sign up to set email alerts
|

Discretization of the Poisson equation with non-smooth data and emphasis on non-convex domains

Abstract: Several approaches are discussed how to understand the solution of the Dirichlet problem for the Poisson equation when the Dirichlet data are non-smooth such as if they are in L 2 only. For the method of transposition (sometimes called very weak formulation) three spaces for the test functions are considered, and a regularity result is proved. An approach of Berggren is recovered as the method of transposition with the second variant of test functions. A further concept is the regularization of the boundary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Notice as well that (3.1) is not a conforming discretization of the very weak formulation of the state equation. However, according to [3,8], its applicability is guaranteed. In our discretized optimal control problem we aim to minimize the objective function…”
Section: A General Discretization Error Estimatementioning
confidence: 99%
“…Notice as well that (3.1) is not a conforming discretization of the very weak formulation of the state equation. However, according to [3,8], its applicability is guaranteed. In our discretized optimal control problem we aim to minimize the objective function…”
Section: A General Discretization Error Estimatementioning
confidence: 99%
“…Numerical experiments confirm the theoretical results.The finite element solution y h is now searched in Y * h := Y h * ∩ Y h and is defined in the classical way: find(1.5)The same discretization was derived previously by Berggren [5] from a different point of view. In [2] we showed that the discretization error estimateholds for s = 1/2 if the domain is convex; this is a slight improvement of the result of Berggren, and the convex case is completely treated. In the case of non-convex domains this convergence order is reduced although the very weak solution y is also in H 1/2 (Ω); the finite element method does not lead to the best approximation in L 2 (Ω).…”
mentioning
confidence: 68%
“…with (w, v) G := G wv denoting the L 2 (G) scalar product or an appropriate duality product. In our previous paper [2] we showed that the appropriate space V for the test functions is…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise conditions on Ω, J and the Banach spaces involved will be given in the subsequent sections. Notice that both the exterior value problems (1.3b) and (1.4b [14,15,17] for the case s = 1). To the best of our knowledge this is the first work that considers the notion of very-weak solutions for nonlocal (fractional) exterior value problems associated with the fractional Laplace operator.…”
Section: Introductionmentioning
confidence: 99%